2022
DOI: 10.1021/acs.jafc.1c07805
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of Phytoalexin Camalexin and Its Derivatives as Novel Antiviral and Antiphytopathogenic-Fungus Agents

Abstract: In response to the invasion of plant viruses and pathogenic fungi, higher plants produce defensive allelochemicals. Finding candidate varieties of botanical pesticides based on allelochemicals is one of the important ways to create efficient and green pesticides. Here, a series of camalexin derivatives based on a phytoalexin camalexin scaffold were designed, synthesized, and assessed for their antiviral and fungicidal activities systematically. Most of these camalexin derivatives exhibited better antiviral act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Further, various novel phosphorylated penta-1,4-dien-3-one derivatives (e.g., 3h , EC 50 104.2 μg/mL, and 3j , EC 50 290.0 μg/mL) and dithioacetal derivatives (e.g., Y21 , EC 50 329.5 ± 1.5 μg/mL) exhibited good antiviral activity against TMV and inhibited TMV activity by binding to TMV CP. In 2021, Guo et al designed and synthesized novel acylurea derivatives (e.g., 7x , EC 50 211.8 μg/mL) with good antiviral activity, which could target TMV CP and inhibit TMV self-assembly thereby suppressing viral infestation . In 2022, Liao et al synthesized a series of camalexin derivatives, screened them against TMV CP, and found that compound 5a caused fusion and disassembly of 20S CP discs, thus affecting the assembly of viral particles . In the same year, Dai et al synthesized a ferulic acid derivative ( D3 , EC 50 38.1 μg/mL) containing β-amino alcohols.…”
Section: Coat Proteins As a Target For Antiviral-agent Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, various novel phosphorylated penta-1,4-dien-3-one derivatives (e.g., 3h , EC 50 104.2 μg/mL, and 3j , EC 50 290.0 μg/mL) and dithioacetal derivatives (e.g., Y21 , EC 50 329.5 ± 1.5 μg/mL) exhibited good antiviral activity against TMV and inhibited TMV activity by binding to TMV CP. In 2021, Guo et al designed and synthesized novel acylurea derivatives (e.g., 7x , EC 50 211.8 μg/mL) with good antiviral activity, which could target TMV CP and inhibit TMV self-assembly thereby suppressing viral infestation . In 2022, Liao et al synthesized a series of camalexin derivatives, screened them against TMV CP, and found that compound 5a caused fusion and disassembly of 20S CP discs, thus affecting the assembly of viral particles . In the same year, Dai et al synthesized a ferulic acid derivative ( D3 , EC 50 38.1 μg/mL) containing β-amino alcohols.…”
Section: Coat Proteins As a Target For Antiviral-agent Screeningmentioning
confidence: 99%
“…60−62 In 2021, Guo et al designed and synthesized novel acylurea derivatives (e.g., 7x, EC 50 211.8 μg/mL) with good antiviral activity, which could target TMV CP and inhibit TMV self-assembly thereby suppressing viral infestation 63. In 2022, Liao et al synthesized a series of camalexin derivatives, screened them against TMV CP, and found that compound 5a caused fusion and disassembly of 20S CP discs, thus affecting the assembly of viral particles 64. In the same year, Dai et al synthesized a ferulic acid derivative (D3, EC 50 38.1 μg/mL) containing βamino alcohols.…”
mentioning
confidence: 99%
“…Indole and its derivatives have received copious attention for their physicochemical and pharmacological properties. Meanwhile, indole derivatives have broad-spectrum biological activities, such as antibacterial, anti-inflammatory, and antiviral. Therefore, commercial products with an indole backbone can be continually searched for in research and development in pesticides and pharmaceuticals. Recent studies have shown that the antiviral mechanism of most indole-containing compounds increases the plant body’s autoimmunity to fulfill disease rebellion. As a promising moiety in this category, 4,5-dihydro-1 H -pyrazoline exhibits diverse activities, which have led to the development of numerous commercially available drugs for application to insecticides, antivirals, herbicides, and fungicides. Thiourea is likewise an active structure, and its most well-known feature is its ability to serve as a hydrogen bond former, which helps strengthen the molecule’s binding to the probable target.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we scrutinized the effect of the reaction conditions on the yield of the target chemical. The results indicated that when the reaction period is less than 2 h, the reaction system produces almost no target chemical; when the reaction feedstock KOH and aminothiourea equivalents are less than 1.5 and 1.5, a substantial increase in reaction time is necessary to increase the target compound yield; the best yields of the target compounds were produced when the reaction materials C1, KOH, and aminothiourea equivalents were correspondingly 1.0, 3.0, and 3.0 for more than 8 h. Then, 1 H, 13 C, and 19 F NMRs and HRMS were used to elucidate the chemical structures of compounds D1−D40 (see Supporting Information).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Natural products (NPs) not only possess diverse structures and pharmacological properties but also have unique effects, easy degradation, or good compatibility with the environment. They have been used by humans as dyes, food additives, drugs, and pesticides for thousands of years. In recent years, the development of NP-based pesticides has become a hot topic. Osthole ( 1 , Figure ) is a naturally occurring coumarin compound found mainly in Apiaceae (Umbelliferae) and Brassicaceae plants . It is highly abundant in the ripe fruit of Cnidium monnieri (L.) Cusson, which is commonly used as a traditional Chinese medicine .…”
Section: Introductionmentioning
confidence: 99%